Rheological and droplet size analysis of W/O/W multiple emulsions containing low concentrations of polymeric emulsifiers - DRAGANA D. VASILJEVIĆ; JELENA V. PAROJČIĆ; MARIJA M. PRIMORAC; GORDANA M. VULETA (Journal of the Serbian Chemical Society, 2009)
Multiple emulsions are complex dispersion systems which have many potential applications in pharmaceutics, cosmetics and the food industry. In practice, however, significant problems may arise because of their thermodynamic instability. In this study, W/O/W multiple emulsion systems containing low concentration levels of lipophilic polymeric primary emulsifiers cetyl dimethicone copolyol and PEG–30 dipolyhydroxystearate were evaluated. The concentrations of the primary emulsifiers were set at 1.6 and 2.4 % w/w in the final emulsions. Rheological and droplet size analysis of the investigated samples showed that the type and concentration of the primary lipophilic polymeric emulsifier markedly affected the characteristics of the multiple emulsions. The multiple emulsion prepared with 2.4 % w/w PEG–30 dipolyhydroxystearate as the primary emulsifier exhibited the highest apparent viscosity, yield stress and elastic modulus values, as well as the smallest droplet size. Furthermore, these parameters remained relatively constant over the study period, confirming the high stability of the investigated sample. The results obtained indicate that the changes observed in the investigated samples over time could be attributed to the swelling/breakdown mechanism of the multiple droplets. Such changes could be adequately monitored by rheological and droplet size analysis.